Bovine Lactoferrin Supplementation Does Not Disrupt Microbiota Development in Preterm Infants Receiving Probiotics. Issue 2 (August 2020) - Grzywacz, Kelly; Butcher, James; Li, Jennifer; Barrington, Keith; Mohamed, Ibrahim; Stintzi, Alain
ABSTRACT: Objective: The aim of the study was to assess whether bovine lactoferrin (bLf) supplementation disrupts intestinal microbiota development in preterm infants less than 31 weeks gestational age receiving prophylactic probiotic administration. Methods: Subjects were recruited from the LACUNA trial (ISRCTN66482337), designed to assess bLf safety. These subjects were randomized to daily receive either probiotic supplements or probiotics supplemented with 100 mg bLf mixed with their feeds (human milk or formula). Stools were collected weekly from enrolled infants for 1 month and the microbiota characterized using V6-16S rRNA gene amplicon profiling. Results: Infants' microbiomes did not increase in alpha diversity over time in both feeding interventions. Infants receiving bLf supplementation had overall higher species richness as compared with those not receiving these supplements and lactoferrin supplementation had differing effects on infant microbiota species richness depending on the infant's gestational age. Principal co-ordinate analysis revealed that the infant microbiotas did not separate by intervention group, gestational age bracket at birth or sampling time and the main factor dictating sample clustering was infant identity. There were very few detectable differences in taxa relative abundance or functional gene content between the microbiotas in the 2 study groups. Conclusions: Bovine lactoferrin supplementation has minimal impact on microbiota composition/function in preterm infants receiving probiotics, and therefore, is unlikely to disrupt microbiota development. Abstract : Supplemental Digital Content is available in the text